ROLE OF INCRETINS IN GLUCOSE HOMEOSTASIS AND DIABETES MELLITUS - DR.P.SATYANARAYANA; N.RATNA KUMARI (International Journal of Pharma and Bio Sciences, 2013)
Incretin hormones are defined as intestinal hormones released in response to nutrient ingestion, which potentiate the glucose-induced insulin response. In humans, the Incretin effect is mainly caused by two peptide hormones, glucose-dependent insulin releasing polypeptide (GIP), and glucagon-like peptide-1 (GLP-1K cells from small intestine secretes GIP and L cell from distal intestine secretes GLP-1.Actions of GIP and GLP-1 is by binding with the receptors.though part of their biological action may also involve neural modulation. GIP and GLP-1 are both rapidly degraded into inactive metabolites by the enzyme dipeptidyl-peptidase-IV (DPP-IV). GLP-1 exerts other significant actions, including stimulation of insulin biosynthesis, inhibition of glucagon secretion, inhibition of gastric emptying and acid secretion, reduction of food intake, and trophic effects on the pancreas. Glucose homeostasis is regulated by of insulin, glucagon ,Cortisol, Growth hormone, and others like incretins. Insulin causes increased uptake of glucose by peripheral tissues and modulation of hepatic glucose production. Glucagon, maintain fasting glucose levels and preventing hypoglycemia. Cortisol, and Growth hormone causes increased production of glucose from adipose tissues. The Incretin hormones regulates glucose homeostasis via augmentation of insulin secretion, inhibiting glucagon secretions, delaying gastric emptying and other glucoregulatory processes.